A Strategy Model for Workplace Mediation Success. (16th November 2021) - Barry, Brian
Abstract : The article proposes a three-step model to help workplace mediators decide on the optimum strategy for mediating workplace disputes. The model uses a grid – the Workplace Mediation Strategy Grid – which is based on a modified version of a grid Professor Leonard Riskin developed for categorising mediation orientations (Riskin 1994; Riskin 1996). The model asks the mediator to first consider the nature of the workplace dispute based on three facets of the dispute. This guides the mediator to plot a position on the Grid which represents two fundamental aspects of strategy for mediating that dispute: (1) how broadly the problem should be defined by the mediator and (2) the style of mediation that the mediator should use. The mediator implements this strategy improving the likelihood of a fair and positive outcome for the disputing parties.